PEMBENTUKAN PORTOFOLIO OPTIMALMENGGUNAKAN SINGLE INDEX MODELPADA SAHAM LQ 45 DI BURSA EFEK INDONESIA (BEI)TAHUN 2014-2016 - I Made Darmayasa (STIE BIITM, 2018)
The research aims to know the optimal portfolio formation using single index model in LQ 45 stocks in the period 2014-2016, to know the proportion of funds used to invest in the optimal portfolio with a single index model and to know return and risk of optimal portfolio with a single index model. This research uses a descriptive research and quantitative approach. The method used in this research is single index model. Samples were taken of 32 companies from LQ 45 index. Samples taken in this study using purposive sampling technique. The result showed that from the 32 samples company elected 26 company that forms composition optimal portfolio with the proportion of shares AKRA 3,9%, WSKT 9%, PTPP 6%, TLKM 12%, GGRM 6,3%, UNVR 7%, BBCA 10%, PWON 4%, ADRO 3,4%, LSIP 1%, UNTR 2,6%, PTBA 2%, ADHI 1,9%, WIKA 2,3%, BBRI 4,5%, SMRA 2,4%, LPKR 1,7%, BMRI 5%, INDF 2,5%, ASII 4%, BBNI 3%, ASRI 1%, BSDE 2,4%, KLBF 2%, MNCN 0,4% and AALI 0,1%. Based on portfolio has formed the result of reckoning return portfolio is 3,9% and risk portfolio 0,0005%.Suggestion from the result of research, investor can invest in 26 of optimal portfolio shares because the resulting return is positive and optimal portfolio risk is much smaller than if investing in one shares only.